Validity and reliability of a Turkish pediatric oral health-related quality of life measure - Raul İ. Garci̇a; Sharon Ri̇ch; Cem Doğan; Judith Jones; İffet Yazıcıoğlu (European Oral Research, 2018)
DOI: 10.26650/eor.2018.53923Purpose